Influence of Promotion and Job Satisfaction on Employee Performance - Razak, Abdul; Sarpan, Sarpan; Ramlan, Ramlan (Journal of Accounting, Business and Finance Research, 2018)
The purpose of this study is to know (1) Promotion of positions held; (2) Employee job satisfaction; (3) employee performance; (4 The influence of promotion and job satisfaction on employee performance in Makasar Government Region, either simultaneously or partially. The method used is descriptive survey method and explanatory. The unit of analysis in this research is the employees of Makassar Government Region, with a sample of 50 people, and the method of analysis used is the frequency distribution and path analysis. Based on the results of the analysis, then obtained as follows, Promotion positions Makassar Government Region has in accordance with the field and expertise, Job Satisfaction employees of Makasar Government Region currently considered satisfied, Employees of Makassar Government Region is considered to have a high enough performance as well as job promotion and job satisfaction affect the performance of employees of Makassar Government Region, but when viewed partially, it turns out the promotion of dominant positions affects their performance.